Comparative analysis of three-dimensional volume rendering and maximum intensity projection for preoperative planning in liver cancer. (2020) - Ho, Joyce L.; Konda, Anuja; Rahman, Jawaria; Harris, Elan; Korn, Ron; Sabir, Aqsa; Bawany, Basil; Gulati, Rajesh; Harris, Gordon J.; Boswell, William D.; Fong, Yuman; Rahmanuddin, Syed
Abstract: Three-dimensional imaging is a useful tool to evaluate liver structure and surrounding vessels for preoperative planning. In this study, we compared two methods of visualizing vascular maps on computed tomography including maximum intensity projection (MIP) and 3D volume rendered (VR) imaging. We compiled important imaging components of pre-surgical planning, and developed criteria for comparison. The imaging techniques were compared based on colorization, volume quantification, rotation, vessel delineation, small vessel clarity, and segmental liver isolation. MIP had more overall limitations due to reduced differentiation of superimposed structures, motion artifact, and interference from calcifications. We determined that because 3D quantitative volume rendered imaging can provide more detail and perspective than MIP imaging, it may be more useful in preoperative planning for patients with liver malignancy. Advanced 3D imaging is a useful tool that can have profound clinical implications on cancer detection and surgical planning.